2011
DOI: 10.1038/labinvest.2011.43
|View full text |Cite
|
Sign up to set email alerts
|

Role of amino acid transporter LAT2 in the activation of mTORC1 pathway and the pathogenesis of crescentic glomerulonephritis

Abstract: Molecular mechanisms and signaling pathways leading to cellular proliferation and lesion formation in the crescentic glomerulonephritis (CGN) remain elusive. In the present study we have explored a potential role of the mammalian target of rapamycin complex 1 (mTORC1) signaling pathway and amino acid transporter (LAT) in the pathogenesis of CGN. Immunohistochemistry and western blot analysis of glomeruli isolated from a rat model of CGN revealed that activation of mTORC1 preceded crescent formation in glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 55 publications
(76 reference statements)
1
48
0
Order By: Relevance
“…Indeed, CXCL12 blockade increased renal mRNA expression levels of nephrin and podocin, two podocyte-slit membrane-related proteins that serve as markers of podocyte differentiation [47], further suggesting that pharmacological treatments can be used to modulate PEC growth and/or differentiation into podocytes. Other potential therapeutic targets for PECs in disease might include epidermal growth factor [48] and its receptor [49], as well as the amino acid transporter LAT2 [50]. More recently, Ueno et al [51] showed that inhibiting Notch in vivo in experimental collapsing FSGS reduced the expression of mesenchymal-like markers including alpha smooth muscle actin, vimentin, and snail.…”
Section: Parietal Epithelial Cells As a Potential Therapeutic Target mentioning
confidence: 99%
“…Indeed, CXCL12 blockade increased renal mRNA expression levels of nephrin and podocin, two podocyte-slit membrane-related proteins that serve as markers of podocyte differentiation [47], further suggesting that pharmacological treatments can be used to modulate PEC growth and/or differentiation into podocytes. Other potential therapeutic targets for PECs in disease might include epidermal growth factor [48] and its receptor [49], as well as the amino acid transporter LAT2 [50]. More recently, Ueno et al [51] showed that inhibiting Notch in vivo in experimental collapsing FSGS reduced the expression of mesenchymal-like markers including alpha smooth muscle actin, vimentin, and snail.…”
Section: Parietal Epithelial Cells As a Potential Therapeutic Target mentioning
confidence: 99%
“…23 Isolated glomeruli were homogenized and lysed on ice in lysis buffer as described above. Protein samples from the glomeruli and cultured podocytes were separated on 7.5% and 4-20% gradient gels under reducing conditions.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Levels of everolimus in the serum samples were measured using the liquid chromatography/mass spectrometry (LC-MS) system (LCMS-2020, Shimadzu) as recently described 23 but with minor modifications. Briefly, serum samples from the rats treated with everolimus or vehicle on day 5 were taken 2 h after gavage.…”
Section: Measurement Of Everolimus Concentrationmentioning
confidence: 99%
“…mTORC1 is negatively regulated by Tsc1/Tsc2 through inhibiting Rheb. Abnormal activation of mTORC1 participates in the pathogenesis of many types of kidney disease, including polycystic kidney disease, diabetic nephropathy (12,18,22,25), podocyte dysfunction, glomerular sclerosis, and kidney fibrosis (4,10,11,14,15,27,30). However, whether mTORC1 signaling activation in podocytes contributes to crescent formation remains obscure.…”
mentioning
confidence: 99%